Como la luz del sol a mediodía: el atributo del sol en la iconografía de santo Tomás de Aquino - Juárez, Guillermo Andrés (Sapientia, 2022)
On the three-year jubilee in honor of Saint Thomas Aquinas, the Dominican friars of the community of Córdoba have considered it appropriate to add the attribute of the sun to the image that occupies the central niche of the altarpiece that bears his name in our basilica, which has led us to further study and explain in greater detail the meaning of such attribute. If the teaching of the Common Doctor has been compared to that of the other doctors as the brilliance of the sun to that of the stars, it is not due only to the depth and breadth with which he illuminated the fields of reason and faith, but also and especially for the way in which he managed to elucidate the relationship between them. Aquinas found in the divine Word the inexhaustible source of that light that radiates over both areas, precisely outlining their own edges and sharply describing their points of convergence and the harmony that exists between them. Comforted by the memory of so eloquent testimonies of the past, we confirm again today that the light with which the Sun of Aquinas shines on the Church and the world, far from being weak as that of a sunset, it is as clear as the light of the sun at noon.